Where is the Force?: Mismatches and Contradictions with Post-Disaster Recovery and Rehabilitation Task Forces - Aira Lynn Mariano Cunanan; Stacey Anne Martinez Panergo; Marian Leigh Coloma Pua; Shanley Carmela Reyes Sandoval; Amanda Sharmaine Ong Soliven (International Journal of Disaster Management, 2022)
The Philippines frequently experiences natural disasters and occasionally man-made ones. As such, Republic Act No. 10121, also known as the Philippine Disaster Risk Reduction and Management Act of 2010, provides designated lead agencies to respond to different stages of disaster management. Despite this, the Philippine government has resorted to the creation of inter-agency task forces (IATFs) to deal with these disasters. These task forces were designed to expedite the implementation of rehabilitation programs and projects. However, in the cases of Task Force Yolanda and Task Force Bangon Marawi, the completion of such programs for typhoon Yolanda and Marawi siege affected areas has been delayed tremendously despite the presence of IATFs. Through an assessment on the effectiveness of the IATFs’ clusters using the multiple case study approach, this paper aims to determine whether or not IATFs were necessary for the recovery and rehabilitation phase of Typhoon Yolanda and the Marawi siege. Upon carrying out the assessment, the lack of timeliness and planning of rehabilitation programs, inconsistencies in the NEDA and OCD reports, insufficient community participation, and the mismatch of services and needs were observed. As such, this paper recommends the creation of criteria for the selection of task force leadership along with other measures that can increase the government’s transparency and accountability through periodical auditing and encourage community participation in rehabilitation initiatives.